Stories, Curriculum Making, and Tension as Support for Identity Shifts: A Narrative Inquiry (LEARNing Landscapes, 2018)
This research is nestled within Huber, Murphy, and Clandinin’s (2011) understanding of curriculum making as situated not only in schools, but also in homes and communities and at the intersections of all three. It also relies on Clandinin, Murphy, Huber, and Orr’s (2010) reconceptualization of tension as a space where educative experiences can occur. An autobiographical narrative inquiry into home, school, and community curriculum making, highlights an educator’s efforts to teach relationally while being wide-awake to how past experiences inform future ones. This inquiry brings to life tension-filled moments and, in so doing, creates a space to know teachers as curriculum makers at home, at school, and in the community. It also suggests one of the values of autobiographical narrative inquiry is the safe space it creates to empathically enter the world of others. Mostly it encourages the reader to think about curriculum making as sentient, ever changing, and as an available support as teachers struggle to sustain their practices.
Keywords: narrative inquiry; curriculum; tension; identities